To match each equation with its solution, we will solve each equation step by step:
-
Equation: \( 3i + 2i - 7 = 18 \)
- Combine like terms: \( 5i - 7 = 18 \)
- Add 7 to both sides: \( 5i = 25 \)
- Divide by 5: \( i = 5 \)
-
Equation: \( 3(2i + 7) = 6i + 21 \)
- Distribute on the left: \( 6i + 21 = 6i + 21 \)
- This is an identity; it has infinitely many solutions (or could be considered as every \( i \) is a solution).
-
Equation: \( 3i + 5 = 3i + 7 \)
- Subtract \( 3i \) from both sides: \( 5 = 7 \)
- This statement is false, so there are no solutions.
-
Equation: \( 3(2i - 7) = 15 \)
- Distribute on the left: \( 6i - 21 = 15 \)
- Add 21 to both sides: \( 6i = 36 \)
- Divide by 6: \( i = 6 \)
-
Equation: \( 3i + 5 = 2i - 7 \)
- Subtract \( 2i \) from both sides: \( i + 5 = -7 \)
- Subtract 5 from both sides: \( i = -12 \)
Now matching each equation with its solution:
- \( 3i + 2i - 7 = 18 \) → \( i = 5 \)
- \( 3(2i + 7) = 6i + 21 \) → infinitely many solutions
- \( 3i + 5 = 3i + 7 \) → no solutions
- \( 3(2i - 7) = 15 \) → \( i = 6 \)
- \( 3i + 5 = 2i - 7 \) → \( i = -12 \)
So the completed matches are:
- \( 3i + 2i - 7 = 18 \) → \( i = 5 \)
- \( 3(2i + 7) = 6i + 21 \) → infinitely many solutions
- \( 3i + 5 = 3i + 7 \) → no solutions
- \( 3(2i - 7) = 15 \) → \( i = 6 \)
- \( 3i + 5 = 2i - 7 \) → \( i = -12 \)